Assessment Of Class II Caries MOD Visited In Hospital: A Three Months Retrospective Analysis. - Agrawal, Ankita; Sinha, Rashmi; Kumar, Suraj; Abhinav, Kumar (Asian Journal of Medical Research, 2019)
Background: Dental caries is a multifactorial oral disease which affects humans of any age, sex, race and socioeconomic status. The present study was retrospectively conducted to assess the prevalence of class II MOD caries patients visited in a department over the period of 3 months. Subjects and Methods: The present study was conducted retrospectively in which record of 250 patients were examined to check the prevalence of Class II MOD cavities. Patients were selected from the out-patient department of Conservative Dentistry. Before commencement of the study permission was taken from ethical committee of the institution.In this study we recorded only class II MOD caries. Results: In our study we examined 250 patients for Class II MOD caries. In 250 patients 76 (30.4%) patients had Class II MOD caries. The class II MOD caries was prevalent in age group 31-40 years (36.84%). Conclusion: Our study concluded that class II MOD was more prevalent than any other carious lesion. The class II MOD caries was prevalent in age group 31-40 years.